The Influence of Principal Prophetic Leadership and Organizational Culture On Teacher Achievement Motivation at Tsanawiyah State Madrasah Teachers In West Jakarta - Bunyamin, Bunyamin; Wahjusaputri, Sintha; N, Isna Oriza (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to analyze, test and obtain a clear picture of the influence of Prophetic Leadership and Organizational Culture on the Achievement Motivation of State Madrasah Tsanawiyah Teachers in West Jakarta. This study used an associative quantitative approach and tested the hypothesis using path analysis with a sample of 159 teachers at Madrasah Tsanawiyah Negeri in West Jakarta. This research shows that: (1) Prophetic leadership has a positive effect on achievement motivation (Y). It was found that the path of direct influence of prophetic leadership on achievement motivation had the regression result equation of ÏY1 =0.464 and t count 6.556, (2) Organizational culture had a positive effect on achievement motivation. It is obtained that the direct influence of organizational culture on achievement motivation, with a regression value of ÏY2= 0.397, while the calculated t value is 5.422, (3) Prophetic leadership has a positive direct effect on organizational culture. It is found that the direct influence of prophetic leadership on organizational culture, the regression result is Ï21= 0.427, and the t-value is 5.909. This research also shows that achievement motivation will increase if prophetic leadership and organizational culture as supporting processes run well.